Franchising from the Perspective of the Transaction Costs Theory - Karolina ORZEŁ (Communications of International Proceedings, 2021)
When analyzing franchise systems as a form of a strategic network of enterprises, the Author referred in her paper to the output of neoinstitutional economics, using Williamson's transaction cost theory (1998), as franchise systems are an effective form of the coordination of the firm's strategic decisions and activities without sacrificing the organizational autonomy. In the first place, they allow to reduce transaction costs related to the coordination of the exchange process both with regard to the end buyer (the market) as well the intraorganization coordination (hierarchy) by increasing innovativeness, flexibility and effectiveness of activities in comparison to alternative solutions (Dworzecki, 2003). The article uses the method of critical analysis of the literature to embed franchise networks in the context of the Transaction Costs Theory (TCT), taking into account, above all, such issues as trust and control
Keywords: Franchising; Transaction Cost Theory; Literature Revive.